Answer : ( 1, - 4 )
Explanation : y=x - 5
y —3х – у = -3
Step 1 : Consider the first eqaution. Subtract X from both sides.
y - x = -5
Step 2 : Consider the second eqaution. Combine y and -y to get 0 .
-3x = -3
Step 3 : Divide both sides by -3
x = -3 / -3
Step 4 : Divide -3 by -3 to get 1
x = 1
Step 5 : Consider the first eqaution. Insert the known values of variables into the equation.
y - 1 = -5
Step 6 : Add one to both sides.
y = -5 + 1
Step 7 : Add negative 5 and one to get negative 4 .
y = -4
Therefore, the answer is ( 1, - 4 )